2020
DOI: 10.1051/0004-6361/202037739
|View full text |Cite
|
Sign up to set email alerts
|

How faculae and network relate to sunspots, and the implications for solar and stellar brightness variations

Abstract: Context. How global faculae and network coverage relates to that of sunspots is relevant to the brightness variations of the Sun and Sun-like stars. Aims. We aim to extend and improve on earlier studies that established that the facular-to-sunspot-area ratio diminishes with total sunspot coverage. Methods. Chromospheric indices and the total magnetic flux enclosed in network and faculae, referred to here as “facular indices”, are modulated by the amount of facular and network present. We probed the relationshi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 84 publications
2
17
0
Order By: Relevance
“…Various studies found the facular area to increase with increasing sunspot area at a diminishing rate such that it appears to gradually saturate (Foukal 1993(Foukal , 1996(Foukal , 1998Chapman et al 1997;Shapiro et al 2014). Solanki & Fligge (1998) and Yeo et al (2020) (hereafter YSK), compared various disc-integrated quantities that are sensitive to the amount of faculae and network present to sunspot area and/or sunspot number and returned analogous results. As first pointed out by Foukal (1993), these results suggest that the balance between the competing effects of bright faculae and network and of dark sunspots on solar irradiance might shift towards the latter as we go from low to high activity levels.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Various studies found the facular area to increase with increasing sunspot area at a diminishing rate such that it appears to gradually saturate (Foukal 1993(Foukal , 1996(Foukal , 1998Chapman et al 1997;Shapiro et al 2014). Solanki & Fligge (1998) and Yeo et al (2020) (hereafter YSK), compared various disc-integrated quantities that are sensitive to the amount of faculae and network present to sunspot area and/or sunspot number and returned analogous results. As first pointed out by Foukal (1993), these results suggest that the balance between the competing effects of bright faculae and network and of dark sunspots on solar irradiance might shift towards the latter as we go from low to high activity levels.…”
Section: Introductionmentioning
confidence: 84%
“…In this section we derive an empirical relationship between the amount of magnetic flux in each newly emerged bipolar magnetic region or BMR, Φ BMR , and the area of the enclosed sunspots, A BMR,S . For this purpose we employ the empirical model of the relationship between the disc-integrated facular and network magnetic flux, ΣΦ FN , and the total surface coverage by sunspots, ΣA S , recently reported by YSK (Yeo et al 2020). The YSK model is given by…”
Section: The Relationship Between the Amount Of Magnetic Flux In Newly Emerged Bipolar Magnetic Regions And The Area Of The Enclosed Sunsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar toTable 1inYeo et al (2020), except with the correct values of h 1 . CaIIK S A 5.030 × 10 −6 0.5854 57.41 8.228 × 10 −2 F Lα S A 7.198 × 10 −7 0.6642 72.34 5.852 × 10 −3 F MgII S A 3.256 × 10 −6 0.7129 54.10 0.1497 F φ S A 1.992 × 10 −4 0.8429 33.46 0.1824 F 10.7 S N1 7.334 × 10 −2 1.073 13.41 65.10 F CaIIK S N1 1.357 × 10 −5 0.7913 34.84 8.243 × 10 −2 F Lα S N1 3.230 × 10 −6 0.7960 49.25 5.861 × 10 −3 F MgII S N1 1.614 × 10 CaIIK S G2 7.421 × 10 −5 0.9240 36.82 8.218 × 10 −2 F Lα S G2 1.564 × 10 −5 1.002 48.40 5.850 × 10 −3 F MgII S G2 8.279 × 10 −5 1.105 34.04 0.1499 F…”
mentioning
confidence: 82%
“…This is a corrigendum to Yeo et al (2020). We had listed the wrong values for the parameter h 1 in Table 1.…”
mentioning
confidence: 94%